Educational Thoughts Of The Genius Thinkers Of The Golden Horde And Nogay Period - Yu.E. Purkhanov (Periodica Journal, 2024)
The article talks about the significance of the pedagogical views of prominent Karakalpak thinkers of the era of the Golden Horde and Nogay period– Soppasli Sipira jirau and Asan Kaygi.
Keywords: Golden; Nogay; jirau; education